The Effect of Applying Mind Mapping Method in Writing Descriptive Text - Nurmala Basri; S Syamsia (Jurnal Langua, 2020)
Writing is one of the four aspects of language skills that a person must possess. By writing, someone can generate interesting ideas and then pour them into writing. The mind mapping method is applied to see how the method influences writing student description texts. This study aims to identify the effect of the mind mapping method on writing descriptive texts for students of SMK Muhammadiyah Tidore Kepulauan. The subjects are students of class XI for the 2020/2021 school year. This study uses a quantitative design. The instrument used by researchers is a test. The analysis technique used to measure student work is by using descriptive text rubrics. The implementation of learning to write descriptive text using the mind mapping method in class XI students is carried out effectively, smoothly, and thoroughly, which can be seen from the seriousness of the students in participating in learning. Previously students were bored, but when learning was done using the mind mapping method, students were enthusiastic and very creative in making mind maps and concentrated very much on writing a descriptive text. The mind mapping method has a positive influence on writing the descriptive text for class XI students of SMK Muhammadiyah Tidore Kepulauan. This can be seen in the learning outcomes that the scores of the results of writing the descriptive text of students using the mind mapping method have increased between the pre-test and post-test scores, the pre-test average score is 51,3 while the post-test average score is 90,6.